The Modulation of Beneficial and/or Harmful Effects of Free Oxygen Radicals in the Context of Molecular Mechanisms Regarding Drug – PART I - Aliev, Gjumrakch (Current Topics in Medicinal Chemistry, 2019)
This special issue of Current Topic in Medicinal Chemistry (CTMC) covers outcomes and ideas for future molecular modifications leading to the novel derivatives with better constructive pharmacological potential for treatment of the different human disorders but also may considering anatomical features of the underlying tissues, and non-chemical based treatment strategies.